Interferon-β-induced pulmonary sarcoidosis in a 30-year-old woman treated for multiple sclerosis: a case report. - Petousi, N; Thomas, E (2012)
UNLABELLED: INTRODUCTION: With the increasing use of recombinant α and β interferon therapy for the treatment of various disorders, cases of interferon-associated sarcoidosis have been reported in the literature. The majority of these have been cases of interferon-α-induced sarcoidosis. We present the first case, to the best of our knowledge, of interferon-induced pulmonary sarcoidosis in a patient whose multiple sclerosis was treated with interferon-β. CASE PRESENTATION: We present the case of a 30-year-old Caucasian woman who presented with unusually persistent bilateral areas of lung consolidation on serial radiographs. Pulmonary sarcoidosis was diagnosed on transbronchial lung biopsy five months after the initiation of treatment with interferon-β for multiple sclerosis. CONCLUSIONS: Sarcoidosis should be considered in the differential diagnosis of a patient who develops clinical or radiological pulmonary disease while undergoing interferon therapy. It is important to note that interferon-induced sarcoidosis, though usually seen in cases with interferon-α, can occur with interferon-β. Neurologists managing patients with multiple sclerosis should be aware of this association between interferon-β and sarcoidosis and promptly refer patients developing respiratory symptoms for further investigation.